Peran Imigrasi Mengenai Pemulangan TKI Di Kota Tanjung Pinang Provinsi Kepulauan Riau - Kustiawan Kustiawan; Nazira Junita Putri; Erta Kurnia Sapitri; Al-Zachra Aprilya Jasmon; Evi Natalia Togatorop; Randa Zaki Saputra (CV. ITTC INDONESIA, 2025)
The high number of repatriations of Indonesian Migrant Workers (TKI) from abroad, especially through Tanjung Pinang City, Riau Islands Province, is a serious challenge for the Indonesian government in its efforts to protect migrant workers. This study aims to analyze the role of immigration in the process of repatriating Indonesian Migrant Workers in Tanjung Pinang in 2024 from an immigration law perspective. The research method used is quantitative normative with a normative and sociological juridical approach, through literature studies, interviews, and field observations. The results of the study show that immigration plays an important role in document checking, identity data collection, and immigration law enforcement to ensure that repatriation is carried out according to regulations and protects the basic rights of Indonesian Migrant Workers. The process of repatriating Indonesian Migrant Workers in Tanjung Pinang involves cross-sector coordination between Immigration, BP2MI, the Social Service, the Police, and other related agencies and faces various challenges such as limited shelter facilities and lack of identity data. Efforts to prevent the departure of Indonesian migrant workers are also carried out through community education, document control, and tightening supervision at ports. This study recommends strengthening synergy between institutions and increasing protection and rehabilitation for Indonesian migrant workers who are repatriated, to reduce the number of non-procedural migrations and maintain the good name and safety of Indonesian citizens abroad.